In-silico characterization and expression analysis of NB-ARC genes in response to Erwinia mallotivora in Carica papaya - Nur Syazana Abu Bakar; Noor Baity Saidi; Lina Rozano; Mohd Puad Abdullah; Suhaina Supian (Penerbit Universiti Kebangsaan Malaysia, 2021)
Disease resistance in plants is commonly associated with resistance (R) genes that encode nucleotide binding site-leucine rich repeat (NBS-LRR) domains that are essential for pathogen recognition and defence signalling. In this study, we identified and analyzed the sequence of putative pathogen-responsive NB-ARC transcripts from Carica papaya transcriptome database, carried out the structural and phylogenetic analysis, and determined the expression profile of the transcripts in C. papaya challenged with Erwinia mallotivora. The findings indicate CpNBS1, the only pathogen-responsive NB-ARC protein identified in this study belongs to the CC-NBS-LRR group. Semi-quantitative PCR showed CpNBS1 was differentially expressed in response to E. mallotivora. Structural analysis of the 4993-Eksotika and 4993-Viorica translated proteins showed striking differences in terms of the number of β-sheets and α-helixes as well their ligand-binding surface, suggesting the role of the LRR domain in determining the specificity of recognition of E. mallotivora effector. Collectively, this study provides new insights into the role of NBS-LRR genes in C. papaya and its implications for enhancing plant disease resistance through genetic engineering.